2003
DOI: 10.1142/s0129183103004346
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Player Game of Life

Abstract: We present a new extension of Conway's game of life for two players, which we call p2life. P2life allows one of two types of token, black or white, to inhabit a cell, and adds competitive elements into the birth and survival rules of the original game. We solve the mean-field equation for p2life and determine by simulation that the asymptotic density of p2life approaches 0.0362.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
0
12
0
2
Order By: Relevance
“…This observation is crucial in developing a mathematical model describing human encounter. To derive such a model we can take an approach similar to the one described in [7], which involves assigning a probability to each possible value that a cell can have after n iterations of the game. From our analysis we have identified that this probability is disproportionately shifted in favour of the extreme possible values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is crucial in developing a mathematical model describing human encounter. To derive such a model we can take an approach similar to the one described in [7], which involves assigning a probability to each possible value that a cell can have after n iterations of the game. From our analysis we have identified that this probability is disproportionately shifted in favour of the extreme possible values.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cunha et al explored this idea in [4] by mapping the location of sensor nodes into a 2D grid and using the energy level and state (whether the sensor node is active or in standby mode) of neighbouring nodes to determine a node's state at the next step of the simulation. A further adaptation [7] describes how a two-player Game of Life progresses under different player strategies.…”
Section: The Game Of Lifementioning
confidence: 99%
“…To illustrate the potential of ASAP as a (mobile) gamification tool, a two-player version of GoL [8], called p2life, has been implemented (see Fig. 6).…”
Section: B a Two-player Game Of Lifementioning
confidence: 99%
“…The rules of the gamified model are described in [8], where the asymptotic behavior of the system is analyzed. The first level model runs without human interplay, that is to say, the system starts from an initial population and its evolution continues without interactions.…”
Section: B a Two-player Game Of Lifementioning
confidence: 99%
See 1 more Smart Citation